Implikasi Yuridis terhadap Calon Independen dalam Pilkada menurut Undang-Undang Tentang Pemilihan Kepala Daerah - Andi Ahmad Mappasiling; Supriyadi Supriyadi (Postgraduate University of Merdeka Malang, 2021)
This legal research is based on the focus of the problem regarding the Juridical Basis of Independent Candidates in the Regional Head General Election System (Pilkada) and the Legal Implications Faced by Independent Candidates in the Regional Head Election (Pilkada) based on the Law on Regional Head Elections. This research includes normative legal research using a statutory approach and a conceptual approach. The conclusion of this study, the juridical basis behind individual candidates in the Pilkada is the Constitutional Court Decision No. 5/PUU-V/2007. The success of individual candidates in participating in regional head elections cannot be separated from the role played by Lalu Ranggalawe, a member of the DPRD in Central Lombok, West Nusa Tenggara who conducted a judicial review of the Constitutional Court. The Legal Implications Faced by Independent Candidates in the Regional Head Election (Pilkada) is the frequent occurrence of difficulties that make prospective candidates from individual candidates fail, especially those of an administrative nature. In addition to the requirements for candidacy which are difficult to fulfill, namely a number of supports from voters, there is also a provision that all support must be factuated by using the census method by meeting directly with each candidate's supporters.DOI: https://doi.org/10.26905/mlj.v2i1.6239